Monitoring of Total Suspended Solid in Coastal Waters due to Conventional Gold Mining Using Multi Temporal Satellite Data, Case Study: Bombana, Southeast Sulawesi - Nurgiantoro Nurgiantoro; Lalu Muhamad Jaelani (Institut Teknologi Sepuluh Nopember, 2017)
Coastal area is an area of transition from terrestrial to marine ecosystems. This area is generally suffered by human, including gold mining activities. The existence of gold in Bombana discovered 2008, making the region as the center of public attention. The appearance of a gold mine in this region other than a blessing, but also brought new problems, especially in coastal areas. Therefore, a routine monitoring is needed to maintain environmental sustainability. Total Suspended Solid (TSS) is one of parameters that are often used for waters quality monitoring. In this research multi-temporal Landsat 8 (2013 to 2015) and in-situ measurement (November 20, 2015) were used to estimate the distribution of TSS. From the analysis, the concentration of TSS in 2014 decreased by 2.88% (36.97 g/m3) and increased by 6.76% (81.64 g/m3) in 2015. The results showed that all estimated-TSS overestimated the permissible water quality threshold (TSS ≤ 80 g/m3), it could be concluded that the gold mining activities in this area has decreased coastal ecological quality.